Istihsan and ITS implementation in the field of Islamic economics and finance - Yogi Kurniawan; Muhajirin Muhajirin (Publikasi Indonesia, 2024)
The primary purpose of this study is to find out the dialectic of Imam Abu Haneefah's legal istinbat method, namely istihsan, then its implementation in the field of Islamic economics and finance. The library research approach is used to conduct research that is carried out with a review of literature, previous research, and other sources related to the problem being studied. The data obtained in this study are primary, as well as data presentation and analysis carried out by researchers based on normative juridical frameworks. The results showed that Istihsan was used as an istinbath method by Imam Abu Haneefa and other scholars because it had a strong foundation both from the Qur'an, Al-Hadith and the views of several other scholars. Thus, the existence of an istihsan can be a postulate of shari'a, although Imam Shafi'i, in his understanding of istihsan categorically rejects it as a postulate of shari'a. Then, the differences in istinbath methods, especially in istihsan, cause many different views about the understanding of istihsan itself, and this causes many legal differences that will result from the method. The implementation of the Istihsan method in the realm of Islamic economics and finance is commonly found in the community in the contract of Shirkah Mufawadhah, Buying and Selling Istishna' and buying and selling credit